Error analysis for grade IX students in completing the materials of quadratic equation - Ika Firmaningsih Dian Prima Sari; Jailani Jailani (Research and Social Study Institute, 2019)
The objective of the study is to discover: (1) types of errors that the students have committed; (2) the obstacles that the students have dealt with; and (3) the size of the errors that the students have committed. The nature of the study is qualitative and quantitative research. Then, within the conduct of the study, the research site was the Angkasa Adisucipto Junior High School located in Janti Street, Adisucipto Air Base, Caturtunggal, Depok, Yogyakarta. The subjects within the study were the students from Grade IX A, Grade IX B and Grade IX C from the Angkasa Adiscucipto Junior High School Yogyakarta. The data were gathered by using test administration, questionnaire distribution and documentation study. Then, the instruments that had been implemented within the conduct of the study were the essay test instrument and the questionnaire. The results of the study show that the errors that the Grade IX students from Angkasa Adisucipto Junior High School in completing the materials of Quadratic Equation from the perspective of conceptual understanding are namely: (1) the students have not correctly formulated the mathematical concepts by using the appropriate symbol or language; (2) the students have committed errors in composing the theorem or formula (whereas it has not been demand-ed in the test items); (3) the students have committed errors in composing the ABC formula when they are completing the test items; and (4) the students have not composed the theorem or the formula for completing the test items. Then, the five biggest obstacles in learning the materials of Quadratic Equation are namely: (1) classroom (64.06%); (2) students’ capacity (46.25%); (3) material delivery (30.07%); (4) students’ attitude and interest toward the materials of Quadratic Equation (29.24%); and (5) students’ motivation (25.78%).